Processos de aprendizagem organizacional na formulação e implementação de estratégias - Caldeira, Adilson (2008)
This study considered the question: How do strategy formulation and implementation happen, which is the contribution of that process to organizational learning development and through what means learning affects the evolution of new strategies formulation and implementation in the organization? A qualitative research was conducted by means of a single case study approach, using interviews, documental analysis and non-participant observation conducted at Petrobras. After presenting the history of company and its strategic planning process, the study discusses how managers see their learning when formulating and implementing strategies, considering four main categories: external and internal environment analysis and resultant learning; strategy formulation and resultant learning; strategy implementation and resultant learning; learning barriers and facilitators. The research reveals that managers see strategy formulation and implementation as a way to provide learning. They also believe that outcoming learning contributes to company's performance by increasing its ability to formulate and to implement new strategies. As a single case study, the research cannot explain all organization behavior and activity as it relates to strategy formulation and implementation and organizational learning. However the study provided a first look at the nature and composition of both phenomena - Learning and Strategy - in the context of an organization.